The Political Consequences of Work: An Integrative Review - Selenko, Eva; Schilbach, Miriam; Brieger, Steven A.; Van Hootegem, Anahí; De Witte, Hans (Journal of Management, 2025)
Work experiences and political participation outside work are intrinsically linked. Management scholars have acknowledged the role that organizations play in shaping political behavior from a firm-level perspective, but the specific working conditions and how they translate into employee political participation and attitudes outside work remain poorly understood. This paper offers an interdisciplinary review of the empirical literature from the past 25 years across the management and political science disciplines. It examines how individual work-related experiences (broadly categorized into job content, working environment, employment characteristics, and social relations at work) relate to political engagement outside of work: political participation, political attitudes, political trust, and political values. The results show that enabling work experiences (e.g., more skill use, autonomy, higher income, more social interactions) and experiences that caused grievances (e.g., more job or financial insecurity) were both related to more political participation but differed in their effect on political trust and regarding political attitudes on economic and cultural issues. We also review the main theoretical explanations and consolidate contradictions. Finally, we propose a future research agenda, calling for the expansion of theoretical lenses, a focus on individual-level explanatory mechanisms, and more multilevel research.